1992
DOI: 10.1172/jci116003
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to steroids in the enhancement of Na+ transport by rat collecting duct cells in culture. Differences between glucocorticoid and mineralocorticoid hormones.

Abstract: It has recently been discovered that both mineralocorticoid (MC) and glucocorticoid (GC) hormones can stimulate electrogenic Na' absorption by mammalian collecting duct cells in culture. In primary cultures of rat inner medullary collecting duct (IMCD) cells, 24-h incubation with either MC or GC agonist stimulates Na+ transport approximately threefold. We have now determined that the effects were not additive, but the time courses were different. As aldosterone is known to stimulate citrate synthase, Na+/K' AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 51 publications
6
28
0
1
Order By: Relevance
“…The major rate limiting step in overall transepithelial Na' transport by the IMCD is the entry of Na+ across the apical (luminal) membrane through a Na+ channel. Steroid hormones such as aldosterone enhance Na+ transport through this channel (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major rate limiting step in overall transepithelial Na' transport by the IMCD is the entry of Na+ across the apical (luminal) membrane through a Na+ channel. Steroid hormones such as aldosterone enhance Na+ transport through this channel (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…The transmonolayer Isc and transepithelial resistance measurements were made in a modified Ussing chamber as previously described (1,2,36) on the day the cells were to be used. For each isolation used for mRNA analysis, parallel cultures were made in the large and the small Millicell filters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The segment-specific cells of the ASDN express a transcellular pathway for Na ϩ reabsorption that is composed of the luminal epithelial Na ϩ channel (ENaC) and the basolateral Na,KATPase (Na ϩ pump). The activity of this Na ϩ reabsorptive pathway is controlled by aldosterone mostly via the mineralocorticoid receptor and to some extent also via the glucocorticoid receptor (5)(6)(7)(8). To prevent these nuclear corticosteroid receptors from being activated by glucocorticoids, the ASDN cells express the 11␤-hydroxysteroid dehydrogenase type 2, which metabolizes glucocorticoids (9).…”
mentioning
confidence: 99%
“…Full efficiency of the urinary concentration dilution process, which is under the control of AVP, requires the concomitant action of glucocorticoids: hydroosmotic permeability of the rabbit CCD has been shown to be synergistically increased by AVP and aldosterone (5). In addition, it has been recently demonstrated that both aldosterone and glucocorticoids are effective in controlling sodium reabsorption in the collecting duct via the MR and also the GR (33,34,35).…”
Section: Discussionmentioning
confidence: 99%